Local Digital Ecosystem: Peran Komunitas Digital dalam Mendorong Bisnis Kreatif Daerah - Siti Fatimah; Wahyu Wibowo; Nur Rahmi Irfaniah; Rita Andriani Harahap; Nur Azizah Panggabean (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
The development of digital technology has opened up new opportunities for the growth of creative businesses in the region, especially through the role of digital communities as social infrastructure that encourages collaboration, knowledge exchange, and commercialization of local products. This article explores the concept of a local digital ecosystem by placing the digital community as a key actor in building a contextual, inclusive, and locality-based digital ecosystem. This study uses a qualitative approach with a literature study method, reviewing the current literature related to digital communities, creative economy, and participatory technologies. The results of the study show that the digital community has a strategic role in strengthening the capabilities of MSME actors and local creators, especially in non-urban areas that are often marginalized by urban-centric narratives. This article offers a conceptual model based on five main elements: Community, Connectivity, Collaboration, Commercialization, and Sustainability (5K), which represents the dynamics of a community-based digital ecosystem. These findings make a conceptual contribution to the study of digital ecosystems with a bottom-up approach, as well as open up space for regional development policies that are more participatory, contextual, and based on local social forces.